Early local impedance drop during pulmonary vein isolation using a novel contact force sensing catheter is associated with acute lesion efficacy. (19th May 2022) - Perge, P; Sallo, Z; Piros, K; Nagy, VK; Osztheimer, I; Merkely, B; Geller, L; Szegedi, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The predictive role of adequate local impedance drop in lesion formation using a novel contact force sensing ablation catheter for pulmonary vein isolation was recently described. The purpose of our pilot study was to assess the temporal characteristics of local impedance drop and its correlation with acute lesion efficacy. Methods: Point-by-point radiofrequency pulmonary vein isolation was performed with 50 W energy setup in power-controlled mode. The efficacy of applications was assessed by pacing along the circular ablation line. We considered the lesions successful if loss of capture was achieved. Local impedance, contact force and catheter position data of the applications with 10 msec resolution was analysed. The local impedance of successful and unsuccessful applications was compared at baseline and 2, 4, 6, 8 and 10 sec time points, respectively. We characterized the local impedance for each time point with the mean of the 5 impedance value closest in time. Results: 184 applications were analysed, 167 were successful and 17 were unsuccessful. There was no difference in mean contact force (p=0.142) and contact force range (p=0.606) between successful and unsuccessful applications. The baseline local impedance was significantly lower in the unsuccessful group (p<0.0001), while successful applications had significantly larger local impedance drop at the 2 (p=0.0006), 4 (p<0.0001), 6 (p=0.0066), 8 (p=0.016) and 10 sec (p=0.0106) time points compared with the unsuccessful group. Local impedance did not change significantly over time in case of unsuccessful applications (p=0.192), while it decreased significantly in case of successful applications (p<0.0001). Conclusion: Early rapid drop of the local impedance may predict effective lesion formation, while slowly changing or unchanged local impedance is associated with unsuccessful applications. In case of a slow local impedance drop during the first 6 seconds of radiofrequency application, it might be reasonable to stop the application and start a new one after catheter repositioning.